Fator de transferência de elementos terras raras em solos tropicais tratados com fosfogesso - Kerley Alberto Pereira de Oliveira (2012)
Approximately 170 million tons of phosphogypsum (PG) are produced annually worldwide and agricultural activities use approximately 15% of this production. This material has been used in agriculture, mainly in Brazilian low vegetation ecosystems (cerrado region). However, this material may contain several toxic elements such as radionuclides and Rare Earth Elements (REE) which can be transferred to soil, plants, and water sources. The objective of this work was to determine the REE transfer factor (TF) of the PG amended soil to lettuce, corn, and soybean. Instrumental Neutron Activation Analysis (INAA) was employed as the method to determine REE contents in PG, soil, and crop samples. The total REE concentration in PG was 4.000 mg.kg-1. The total REE concentration in soil samples were 26 mg.kg-1 in sandy soil and 280 mg.kg-1 in clayey soil. These results showed that PG is a REE concentration waste. Transfer factors for REE to corn, from two types of amended soils, were below detection limits. The REE transfer factor from clayey soil to soybean was 0.0003 0.0006 of La. TF of La from clayey soil to lettuce was 0.002 - 0.007 and 0.05 1.44 from sandy soil. Different doses of PG used in soil samples did not influence REE transferfactors. The really important factor in REE Transfer Factor was the type of soil. The REE intake dose was 6,04 mg.ano-1.